Extrafollicular odontogenic adenomatoid tumor: a case report - Queija Saldaña, Martín Alexander (2020)
Odontogenic adenomatoid tumor (OAT), is a rare, benign, non-invasive, represents 3% of all odontogenic tumors. It presents follicular, extrafollicular and peripheral variants, the follicular variant with an included tooth is the most common. The objective of this article is to present a case of TOA in a 13-year-old female patient, located in the upper left canine region. After extrabuccal examination, slight swelling was observed, causing loss of definition of the left nasolabial fold, on intrabuccal examination, swelling of the vestibular bone table was observed between elements 2.2 and 2.3 with dislocation of the same, causing diastema, the tomographic examination identifies hypodense image with well-defined hyperdense borders, with internal calcifications. Incisional biopsy was performed, which resulted as diagnosis an extrafollicular TOA. The enucleation of the tumor was proceeded. In a 24-month follow-up, it is possible to observe bone regeneration without signs of recurrence.